Peningkatan Hasil Belajar Siswa melalui Metode Fun Learning dalam Pembelajaran Tematik - Eli Mufidah; Nurul Aminatus Sa’diyah (IBTIDA', 2020)
The phenomenon that occurs in one of the Sekaran Public Elementary Schools shows that students have decreased learning outcomes in Thematic learning and have not achieving the minimum completeness criteria (KKM) value. Students are less enthusiastic in participating in learning because of their low learning motivation, even some students do not want to learn and do not want to go to class. This study aims to describe the effect of the Fun learning method in “Kebersamaan” theme to improve student learning outcomes in grade II in Sekaran State Elementary School. This study uses the research design "One group pre-test and posttest design" so that only requires one class without a control class that is only in class II, amounting to 15 students. Researchers used the test as a research instrument which was then analyzed using the Pearson Product Moment formula and Paired Sample t-test. Based on the results of data analysis using Pearson Product Moment, the correlation between the variables Fun learning methods with learning outcomes = 0.713. After comparing with "r table = 0.553", Ho is rejected and Ha is accepted, which means that the Fun learning method has an effect in improving student learning outcomes at Sekaran State Elementary School. While the Paired Sample t-test significance test, showed a correlation number before the Fun learning method was applied after being applied at 0.713> α (0.05). based on these values, the Fun learning method influences the learning outcomes of Grade II students in Sekaran State Elementary School significantly